Contact dermatitis is an unrecognized problem in the construction industry: Comparison of four different assessment methods. Issue 10 (18th August 2017) - Timmerman, Johan G.; Heederik, Dick; Spee, Ton; van Rooy, Frits G.; Krop, Esmeralda J. M.; Rustemeyer, Thomas; Smit, Lidwien A. M.
Abstract : Background: A high contact dermatitis symptoms prevalence has been observed in Dutch construction workers. Methods: Contact dermatitis was diagnosed by an expert panel using questionnaire data and photographs of 751 subjects' hands. A subset was evaluated by two occupational physicians. Their diagnoses were compared to those of the expert panel. In addition, two self‐reported questionnaire‐based assessment methods were compared to the expert panel evaluation. Associations between contact dermatitis and determinants were assessed using log‐binomial regression analysis. Results: Contact dermatitis prevalence was high: 61.4% (expert panel's diagnosis) and 32.9% (self‐reported). Agreement between occupational physicians and the expert panel was low but increased after training. Washing hands with solvents and performing job‐related tasks at home were related to contact dermatitis. Conclusions: Contact dermatitis prevalence among construction workers is high. Recognition of contact dermatitis by occupational physicians is poor but can be improved by training. Awareness of skin disorders should be raised.